Diversity of bacterial and fungal endophytes in maize and their larvicidal effect against the spotted stem borer Chilo partellus. Issue 11 (1st November 2020) - Kebede, Denberu; Alemu, Tesfaye; Tefera, Tadele
ABSTRACT: The present study aimed to (i) determine the distribution of endophytes in selected genotypes, growth stages and parts of maize; (ii) evaluate the larvicidal effect of the endophytes against the spotted stem borer Chilo partellus and (iii) determine the level of colonisation of maize by endophytes. Compared with hybrid and landrace maize, open pollinated variety (OPV) maize exhibited a relatively diversified composition of endophytic bacteria. Among the 39 maize endophyte isolates screened for insecticidal antibiotic production, 11 (8 bacteria and 3 fungi) showed larvicidal activity against C. partellus . Isolate aueb-11 from the genus Bacillus showed the highest mortality (75.93%) against C. partellus . The bacterial isolates varied in terms of their activity to colonise the plant parts, and this was assessed using leaf and seed inoculation methods: in the foliar spray method, the maximum bacterial density recovered from the leaf and stem samples were 9.6 × 10 2 and 9.2 × 10 2 colony forming units per gram of sample, respectively. These effective isolates could be promising larvicide against C. partellus .